2019
DOI: 10.21037/jtd.2019.07.09
|View full text |Cite
|
Sign up to set email alerts
|

Salvage resection of advanced mediastinal tumors

Abstract: The surgical treatment of locally advanced mediastinal tumors invading the great vessels and other nearby structures still represent a tricky question, principally due to the technical complexity of the resective phase, the contingent need to carry out viable vascular reconstructions and, therefore, the proper management of pathophysiologic issues. Published large-number series providing oncologic outcomes of patients who have undergone extended radical surgery for invasive mediastinal masses are just a few. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Some studies have shown that patients with advanced thymoma, in whom preoperative examination confirms that resection of their tumor is not achievable, should be treated with induction chemoradiotherapy to improve the feasibility of complete surgical resection 7,9,14,18,20 . However, studies on the therapeutic effect of preoperative induction chemoradiotherapy for patients with advanced thymoma invading the SVC is still limited, 3,6,21,23 and whether preoperative induction therapy will affect the patency of vascular grafts is a concern for many clinicians 16,24–26 . Extensive resection of malignant thymic tumors combined with reconstruction of SVC and left innominate vein have been reported to be beneficial, 16,25–26 but there are few reports on induction chemoradiotherapy before thymoma resection and SVC replacement and reconstruction surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have shown that patients with advanced thymoma, in whom preoperative examination confirms that resection of their tumor is not achievable, should be treated with induction chemoradiotherapy to improve the feasibility of complete surgical resection 7,9,14,18,20 . However, studies on the therapeutic effect of preoperative induction chemoradiotherapy for patients with advanced thymoma invading the SVC is still limited, 3,6,21,23 and whether preoperative induction therapy will affect the patency of vascular grafts is a concern for many clinicians 16,24–26 . Extensive resection of malignant thymic tumors combined with reconstruction of SVC and left innominate vein have been reported to be beneficial, 16,25–26 but there are few reports on induction chemoradiotherapy before thymoma resection and SVC replacement and reconstruction surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Invasion to mediastinal structures is one of the clinical features of advanced thymic tumors. Because of its aggressive behavior, thymic tumors may invade adjacent organs or large vessels, such as the superior vena cava (SVC), innominate veins and pericardium, etc 3 . In recent years, several reports have described surgical resection with SVC reconstruction for the treatment of advanced thymic tumors 4,5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation